The Relationship of Nutritional Status and Anxiety with Menstrual Syndrome in Midwifery Study Program Undergraduate Program University dr. Soebandi - ajeng dea damayanti (LPPM Universitas dr. Soebandi, 2023)
Background : Menstruation is the process of shedding the uterine lining which is followed by continuous bleeding that occurs every month, which in turn creates the menstrual cycle. Menstrual disorders can be caused by several things, including psychological (stress, tension from everyday life, anxiety, and physical and mental fatigue), hormonal, nutritional problems, and organic (inflammation of tumors, trauma, etc.). Research Method : This research method uses cross sectional method. Sampling using total sampling. The sample is 37 respondents. Statistical analysis using the Chi-square test. Research Result : Analysis of the Relationship of Nutritional Status and Anxiety with Menstrual Syndrome in Midwifery Study Program Undergraduate Program University dr. Soebandi. The results of statistical tests using the Chi-Squre calculation using SPSS 25 obtained the results of P-value 0,415 > a = 0,05 dan 0,139 > a = 0,05. Conclusion : Then Ha is accepted and Ho is rejected, which means there is no relationship between nutritional status and anxiety with menstrual syndrome. Suggestion: it is expected to pay more attention to stress management so that the anxiety experienced does not drag on.